Kurdistan Region of Iraq : Economic and Social Impact Assessment of the Syrian Conflict and the ISIS Crisis - World Bank (Washington, DC, 2015)
The development objective of the Kurdistan Regional Government (KRG) economic and social impact assessment is to provide the Iraqi Government with an impact analysis of the current crisis at the regional level. This will provide a foundation for international efforts to assist the KRG in its efforts to rally humanitarian support. The events which motivate this study include: the Syrian civil war, which began in 2011; and the insurgency of the ISIS (Islamic State in Iraq and Syria) group, which began in June 2014. The violence and atrocities associated with each of these two events caused tens of thousands to flee their homes and many chose the relative safety of Kurdistan Region of Iraq (KRI), as refugees from the Syrian conflict and as internally displaced persons (IDPs) from the ISIS crisis. These events took place in the context of the fiscal crisis, which caused about a 90 percent drop in fiscal transfers from the central government in Baghdad starting in early 2014. This report provides the government with a technical assessment of the impact and stabilization costs associated with the influx of refugees and IDPs. Impact refers to the immediate economic and fiscal effects on the KRG economy and budget, while stabilization cost refers to the additional spending that will be needed to restore the welfare of residents of the KRI. The report is the outcome of a process in which a World Bank team engaged intensively on the ground with regional government institutions and international partners to gather and mobilize data from disparate sources into a structured narrative and integrated technical presentation from which all stakeholders can draw to help them design and implement strategies for coping with the crisis.